USE OF SEQUENCING METHODS FOR SPECIES IDENTIFICATION EXEMPLIFIED BY PHYLOGENETIC RELATIONSHIPS WITHIN GENUS HEDYSARUM L. - D. R. Imachueva; F. K. Serebryanaya; E. M. Machs; V. V. Kotseruba (Фармация и фармакология (Пятигорск), 2021)
At the moment, a relevant objective in pharmacognosy, is the use of all kinds of the DNA analysis methods for identifying plant materials, detecting counterfeits, genetically modified crops and products.The aim of the research is to study the possibility of using molecular genetic research methods in the analysis of the genus Hedysarum L., for the identification of medicinal plant materials. This article presents the results of the application of molecular genetic research methods in the analysis of the genus Hedysarum L. in the flora of the North Caucasus.Materials and methods. The study material was the samples of the genus Hedysarum L. species collected in the North Caucasus: Hedysarum caucasicum M. Bieb. (in the fruiting phase in the territory of the Karachay-Cherkess Republic); Hedysarum grandiflorum Pall. (in the fruiting phase in the Volgograd region); Hedysarum daghestanicum Rupr. ex Boiss. (in the flowering phase in the Republic of Dagestan).  Sequencing of the ITS1-5.8S-ITS2 marker region of gene 5.8S by the RNA ribosome was carried out according to the Sanger method on the AbiPrism 3130 genetic analyzer at the laboratory of biosystematics and cytology of Komarov Botanical Institute of the Russian Academy of Sciences.Results. Based on a comparative study of the marker region of the nuclear ribosomal gene 5.8S rRNA, marker nucleotide substitutions of Hedysarum caucasicum M. Bieb., Hedysarum daghestanicum Rupr. ex Boiss., Hedysarum grandiflorum Pall, have been identified. The most probable secondary structure of 5.8S rRNA has been constructed. It has been shown that based on the analysis performed, it is possible to predict additional raw material sources of mangiferin and other groups of xanthones using the molecular data exemplified by the Obscura section.Conclusion. Based on the data obtained, it can be concluded that the morphological classification of the genus Hedysarum L. can be confirmed within the Obscura section.